Women’s Empowerment in Agrifood Governance (WEAGov) - Ragasa, Catherine; Kyle, Jordan (CGIAR System Organization, 2024)
The Women’s Empowerment in Agrifood Governance (WEAGov) is a diagnostic tool developed by IFPRI to help evaluate the extent to which women are empowered across the policy cycle related to agrifood systems. WEAGov provides a way for national policymakers, civil society organizations, and researchers to identify gaps and opportunities to raise women’s voice and agency at different stages of the policy cycle, and provides a basis for monitoring progress in women’s empowerment in agrifood systems governance over time.